A new genus and species of Tarsonemidae (Acari: Heterostigmata) from the Atlantic Forest, Brazil - Lofego, Antonio C. [UNESP]; Demite, Peterson R.; De Moraes, Gilberto J. (Magnolia Press, 2015)
Kaliszewskia ochoai gen. nov., sp. nov. (Tarsonemidae: Tarsoneminae: Tarsonemini) is described from adult females, collected on Blepharocalix salicifolius (Kunth) O.Berg and Plinia sp. (Myrtaceae), from the Atlantic Forest in Brazil.
Keywords: Biodiversity; Neotropics; Tarsonemoidea; Taxonomy